2016
DOI: 10.13189/ujmsj.2016.040104
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Knowledge and Attitude of Developing Country Pregnant Mothers about Anesthesia for Cesarean Section

Abstract: Knowledge about a type of Anesthesia to be used for cesarean section is not well investigated in developing countries. Knowing types and complications of anesthesia for Caesarean section will help mothers to have less stress and decide on their anesthetic choice. This study aimed to assess perception, knowledge and attitude of pregnant mothers towards Anesthesia for Cesarean section. A hospital-based cross-sectional study was conducted to assess knowledge and attitude of pregnant mothers attending antenatal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 7 publications
2
14
2
2
Order By: Relevance
“…Accordingly, pregnant women who have had previous operation or exposure to anesthesia were 5 times more likely to have good knowledge about anesthesia for CS as compared to pregnant women who hadn't any previous operation. This nding is consistent with studies conducted in Jimma University specialized Hospital Ethiopia (17), India (20), Pakistan (13,23) Turkey (24), and Nepal (25) which showed that patient with previous exposure of anesthesia or surgery had good knowledge of anesthesia techniques as compared to those without previous exposure. This might be due to that pregnant women who have had previous operation or exposure to anesthesia may spend more effort to get accurate information about it which improves their knowledge level towards anesthesia.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Accordingly, pregnant women who have had previous operation or exposure to anesthesia were 5 times more likely to have good knowledge about anesthesia for CS as compared to pregnant women who hadn't any previous operation. This nding is consistent with studies conducted in Jimma University specialized Hospital Ethiopia (17), India (20), Pakistan (13,23) Turkey (24), and Nepal (25) which showed that patient with previous exposure of anesthesia or surgery had good knowledge of anesthesia techniques as compared to those without previous exposure. This might be due to that pregnant women who have had previous operation or exposure to anesthesia may spend more effort to get accurate information about it which improves their knowledge level towards anesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…It was higher than studies conducted among pregnant women on knowledge and attitudes towards anesthesia for CS in Tikur Anbessa Specialized Hospital Ethiopia (32%) (11), Jimma University Specialized Hospital (31.3%) (17), India (30.0%) (21), and Khamis Mushait (37.5%) (14). The reason for high prevalence of knowledge in this study as compared with Tikur Anbessa Specialized Hospital might be due to majority (92.7%) of the study participants in this study were from urban areas while only 42.5% of participants from Tikur Anbessa Specialized Hospital were from urban set up.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations